Recorrido histórico del concepto de función y de las funciones de diseño desde la teoría del diseño industrial (2021)
This project seeks to find the foundations of function concept´s within the framework of industrial design. At the same time, the theory of the product language and the different authors who have considered functions in their subdivision to explain what should be the elements that a designer must take into account when they are in the designing process or projecting a product and / or service. All this in order to clarify the functions and the different elements considered within the proposal, leaving a couple of questions that would be interesting to discuss within the design academy.